Analisis kebutuhan alat peraga edukatif di Sekolah Luar Biasa - Ishartiwi, Ishartiwi; Handoyo, Rendy Roos; Dewi Barotut Taqiyah (Piramida Akademi, 2024)
This study used a descriptive qualitative approach with the aim of exploring an in-depth understanding of the use of educational aids (APE) in special schools (SLB) in Yogyakarta Special Region. This study involved 70 special education teachers with diverse educational backgrounds and teaching experiences. Interviews and observations were used to collect information. Data were analyzed using needs analysis techniques to identify the specific needs and preferences of students with special needs in the context of learning. The results showed that APE has an important role in supporting the learning of students with special needs. Although some SLBs have allocated funds for the purchase of APE and implemented policies related to its use, there are still challenges in terms of availability, compatibility with students' specific needs, and maintenance of existing APE. Different types of specific barriers, such as visual, hearing, intellectual, physical, emotional and behavioral barriers, require different approaches in the development and use of APE. For example, for students with visual impairments, APE should optimize the use of the senses of touch and hearing, while for students with emotional and behavioral impairments, APE should focus on developing positive behaviors and managing emotions.